Analisis Kontingensi Saluran Transmisi 150 kV pada Subsistem Jambi - Ahmad Rifki Nazwan; Dasrinal Tessal; Andre Rabiula (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
High-voltage electrical systems are essential for maintaining a stable and efficient electricity supply. However, increasing capacity and expanding networks increase the risk of disruptions that can trigger blackouts. System reliability relies heavily on its ability to survive sudden disturbances, such as loss of generation or transmission line breaks. Contingency analysis (N-1) is used to predict system conditions and design appropriate mitigations to improve reliability. This study analyzes contingency in the Jambi 150 kV subsystem using the Newton-Raphson method in ETAP 19.0.1 software, with a Performance Index (PI) approach. The results show the Muara Bulian - Aurduri line has the highest PI (4.3382), while Aurduri - Muara Sabak has the lowest (1.4754). Contingency on the Aurduri - Muara Bulian line causes low voltage at the Sarolangun and Muara Bulian buses, 130.376 kV and 131.193 kV respectively. In addition, there is a redistribution of power flow that increases the load by 20.42% on the Muara Tebo - Aurduri line. As a mitigation measure, the installation of shunt capacitors of 5.807 MVar at Sarolangun bus and 23.074 MVar at Muara Bulian is recommended